Studi Etnobotani Tumbuhan Kosmetik Alami Masyarakat Suku Dayak Kanayatn Desa Sebatih Kecamatan Sengah Temila Kabupaten Landak - Elvi Rusmiyanto Pancaning Wardoyo, Evi Noviantina, Riza Linda, (Universitas Tanjungpura, 2018)
The use of plants as cosmetic ingredients has been utilized by the Dayak Kanayatn Tribe Society in Sebatih Village of Sengah Temila Sub-district of Landak Regency. The purpose of this study was to investigate species of plants, parts of plant, locations of plant, and value of informant agreement ratio of society understanding on the use of plants for natural cosmetic. This study was conducted for three months, from May to July 2017 in Sebatih Village of Sengah Temila Sub-district of Landak Regency. To determine the sample of study, purposive sampling was applied and semi-structured interview was employed to collect the data. Quantitative analysis of this study was operated by calculating frequency of citation, ratio of informant agreement, percentage of plants of plant, and the percentage of plant habitats. The findings indicate that Dayak Kanayatn Tribe Society in Sebatih Village utilize 16 plant species that embrace in 14 plant families for natural cosmetic. The utilization of plants for natural cosmetic is divided into 5 categories, particularly 2 plant species of bodycure, 7 plant species for facial, 1 plant species of healthy nails, 3 plant species for mounth clean and 5 plant species for hair treatments. Leaf is the main part of plants that is mainly used for cosmetic or approximately 43.75%. The highest value of citation frequency value in this study 100%, specifically areca nut (Areca catechu), henna (Impatiens balsamina), guava (Psidium guajava) and coconut (Cocos nucifera). Society’s level of understanding on the utilization plant for cosmetic, specifically for healthy nails achieve the highest value on informant agreement ratio (RKI), namely 1 and the lowest value of informant agreement rasio (RKI) is 0.96.